Integrasi Nilai Islam dan Kearifan Lokal dalam Membentuk Sikap Inklusif Guru Roudlatul Atfal - Tihnike, Dona; Makhzuniyah, Minhah; Rahmawati, Indriana (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study to testing the Inclusive Islamic Education Model Based on Lokal Wisdom by analyzing the relationship between Islamic values, local wisdom, and teachers’ inclusive attitudes at Raudlatul Athfal (RA) in Pasuruan Regency. Using a quantitative correlational design, data from 90 teachers were collected through validated scales. The results of the Pearson correlation test showed a strong positive relationship between local wisdom and inclusive attitudes (r = 0.682, p < 0.01), while Islamic values also correlated significantly with inclusive attitudes (r = 0.615, p < 0.01). Multiple regression analysis indicated that local wisdom significantly affected inclusive attitudes (β = 0.523, t = 6.321, p < 0.001), while Islamic pedagogical competence contributed moderately (β = 0.314, t = 2.987, p < 0.01). These findings highlight that inclusive attitudes are shaped not only by pedagogical skills but also by the internalization of Islamic and cultural values. The model’s integrates spiritual, cultural, and professional dimensions to promote inclusive, empathetic, and contextually grounded Islamic education.